Yield and gap analysis of wheat productivity through frontline demonstrations in Jhunjhunu district of Rajasthan - Verma, R.K.; Nand, Daya; Rathore, R.S.; Mehta, S.M.; Singh, Mahendra (Annals of Agricultural Research, 2014)
Front line demonstrations on wheat variety Raj-4083 were conducted on farmers' fields in district Jhunjhunu (Rajasthan) during rabi season of the year 2010-11, 2011-12 and 2012-13. About 10.95 per cent higher grain yield was recorded under demonstrations over the farmers' practices. The extension gap, technology gap and technology index were observed to be 409 kg per ha, 359 kg per ha and 7.98%, respectively. An additional return of Rs. 7887 per ha was obtained with an additional investments of Rs.1552 per ha coupled with scientific monitoring of demonstrations and use of other non-monetary factors. Fluctuating MSP and or sale price of wheat during different years also influenced the economic returns per unit area. On average basis, the incremental benefit: cost ratio was found as 5.08.